2020
DOI: 10.1002/essoar.10503641.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Surface currents and significant wave height variability: a numerical investigation of the Agulhas current region

Abstract: Advances in the understanding and modelling of surface currents have revealed the importance of internal waves, mesoscale and submesoscale turbulence. Indeed all these features should have a large influence on wind waves, and in particular wave heights are expected to be modified by refraction. Still, the quantitative impact of currents on waves is not well known due to the complexity of the random wave fields and currents that are found in the ocean, and the lack of observations of both currents and waves at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In this section the spatial variation induced by the currents and the scale at which they impact the wave propagation are analysed for the present application. It was shown in Ardhuin et al, 2017 andMarechal andArdhuin, 2020 that currents have an impact at short spatial scales, between 10 km and 100 km. These two studies focus on two strong boundary currents (Agulhas and Gulf stream respectively).…”
Section: Spatial Variabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…In this section the spatial variation induced by the currents and the scale at which they impact the wave propagation are analysed for the present application. It was shown in Ardhuin et al, 2017 andMarechal andArdhuin, 2020 that currents have an impact at short spatial scales, between 10 km and 100 km. These two studies focus on two strong boundary currents (Agulhas and Gulf stream respectively).…”
Section: Spatial Variabilitymentioning
confidence: 99%
“…More recently, there has been some interest in the interaction with currents, which for the most part highlights the refraction induced by current gradients. The impact of large-scale currents like the Agulhas current or the Gulf Stream is well documented through numerical simulations cross-checked with satellite observations -see for example Marechal and Ardhuin, 2020;Barnes and Rautenbach, 2020 for recent studies on the Agulhas current. The impact of small scale currents has drawn less attention but in Ardhuin et al, 2017 it is shown that even submesoscale structures with shorter length scales (ranging from 10 km to 100 km) can explain the majority of the significant wave height spatial variability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation